IMPROVE TEACHER PERFORMANCE THROUGH STRENGTHENING COMPETENCE - mohamad akuba; Heldy Vanni Alam (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
Teacher performance is fundamental in order to maintain and improve the quality of education at all levels of education. As the spearhead and main actor in creating human resources in schools, it is necessary for teachers to get strengthening in their competence aspects. Therefore, the purpose of this study is to examine in depth the efforts to improve teacher performance through strengthening their competence. The approach used in this research is quantitative research by examining the results of the distribution of questionnaires to high school teachers as many as 55 people as the main respondents in Gorontalo Regency. Data were collected using SPSS version 24 and analyzed using simple linear regression. The author believes that through strengthening the competence of teachers, their performance can increase. The author's belief is evident from the processed field data, it turns out that the contribution of variable X (Competence) to Y (Teacher Performance) is 0.374 or 37.4%. Therefore, if teacher competence is improved, it will immediately improve teacher performance in schools in general and more specifically in the teaching and learning process. This result is also supported by the results of previous research conducted by Sedayu 2019 where competence affects the performance of SMK teachers by 0.556 or 55.6%.